PENGARUH FOREIGN DIRECT INVESTMENT (FDI), EKSPOR DAN IMPOR TERHADAP PERTUMBUHAN EKONOMI INDONESIA 1998-2017 - Bagaskara Prawira; Sudati Nur Sarfiah; Gentur Jalunggono (DINAMIC : Directory Journal of Economic, 2019)
This study aims to determine the effect of foreign direct investment (FDI), exports  and  imports  on  economic  growth  in  Indonesia  in  1998-2017.  This research is classified as quantitative descriptive research. The data in this study uses time series data analysis with multiple linear regression analysis techniques, R2 test, t test and F test. The results of the study show that: 1. The foreign direct investment (FDI) variable partially shows that there is a significant effect on the variable economic growth in Indonesia. 2. The export variable partially shows that there is a significant influence on the variables of economic growth in Indonesia. 3. The import variable partially does not show a significant effect on the variable economic growth in Indonesia. 4. Variable foreign direct investment (FDI), exports, and imports together show a significant influence on the variables of economic growth in Indonesia Keywords: FDI, Exports, Imports, Economic Growth.